PERFORMANCE OF THE POPULATION AND CIVIL REGISTRATION SERVICES IN FAMILY CARD MANUFACTURING SERVICES IN NORTH MOROWALI DISTRICT - Astriana, Yuyun; Hasbullah, Hasbullah; Nuraisyah, Nuraisyah; Haryono, Dandan (Penerbit Lafadz Jaya, 2024)
The aim of this study is to determine the Performance of the Population and Civil Registration Office in Family Card Services in North Morowali Regency. This research employs a qualitative approach through observation, in-depth interviews, and documentation as data collection techniques. Informants were selected using purposive sampling technique, including the Secretary, Head of Dafduk, Head of Pencapil, Population Identity Officer, and a representative of the community. Data analysis techniques include data collection, data display, data condensation, verification, and drawing conclusions. The results show that in the Family Card Services at the Population and Civil Registration Office in North Morowali Regency. Employees have demonstrated good technical skills, including knowledge of task execution, and equipment usage, acquired through training in the office. Employees have been able to understand the complexity of the organization and adapt to their tasks and responsibilities. However, abilities in interpersonal relationships, such as cooperation, motivation, and negotiation, still need improvement. In conclusion, although the Population and Civil Registration Office in North Morowali Regency has shown progress in the technical and conceptual abilities of its employees in Family Card Services, there is still room for improvement in interpersonal relationship skills. It is important to pay special attention to cooperation, motivation, and negotiation skills among employees to enhance the effectiveness and efficiency of services and advance the organization as a whole.